Gelatin micro‐ and nanocapsules obtained via sonochemical method. Issue 48 (2nd July 2020) - Yankova, Iveta; Shestakova, Pavletta; Reis, Rui L.; Pashkuleva, Iva; Vassileva, Elena
Abstract: Gelatin capsules (GCs) with mean size between 200 and 400 nm are prepared via sonochemical method. Their size is low that the usual size for the sonochemically obtained protein capsules and depends on the preparation conditions. The nanometer size of GCs is explained by the low‐gelatin concentration and by the denaturated state of gelatin. The influence of pH, sonication time, and temperature on GCs size is investigated. An increase in temperature and sonication time results into GCs size increase. The pH dependence of GCs size passes through a minimum at the isoelectric point of gelatin. The broad size distribution detected by dynamic light scattering and scanning electron microscopy is explained by the broad molecular weight distribution of gelatin. GCs are successfully applied for encapsulation of two hydrophobic drugs, α‐tocopherol and acetylsalicylic acid, in order to demonstrate the versatility of the sonochemical method for drug encapsulation. In the case of α‐tocopherol drug entrapment efficiency as high as 95% is obtained. Abstract :